Private health insurance and hospitalization under Japanese national health insurance - Tetsuji Yamada; Chia-ching Chen; Tadashi Yamada; Haruko Noguchi; Matthew Miller (The Open Economics Journal, 2009)
We empirically examine how the decision to purchase private health insurance and hospitalization are made based on labor income, socio-demographic factors, and private health insurance. The increase in household labor income and wealth has a positive effect on purchasing private health insurance. This suggests a supplementary effect for public health insurance under the strict control of a two-tier healthcare coverage system. Our results support the hypothesis that moral hazard presents for the costs paid to private health insurance by households. A strong positive association with the risk of hospitalization causes individuals to change their health behavior after purchasing private health insurance leading to lower costs in the ill health status and acquire less preventive measures. Thus, moral hazard exists in Japanese health insurance market. Unlike the previous study, adverse selection based on our results is not negligible in the case of hospitalization in Japan. The positive effect indicates that the higher the risk of illness with households, the more insurance policies a household possesses. The results support our hypotheses that the decision to purchase health insurance in case of death in an insured household in a hospital is attributed to the initial health stock of the household. This means that households purchase private health insurance when there is a high probability of hospitalization with claimed insurance on death. The benefits from private health insurance policies for hospitalization provide incentives for individuals to purchase health insurance that are a reflection of adverse selection against private health insurance.
Keywords: 330